Wavelet Packet Assisted Genetic Algorithm Based ISI-ICI Suppression for OFDM Systems - HASAN, ALAA ABDULAMEER (Nahrain University College of Engineering Journal, 2017)
In this paper, the behavior of Wavelet Packet-Orthogonal Frequency Division Multiplexing (WP-OFDM) system based on Genetic Algorithm (GA) to mitigate both the Inter-Symbol Interference (ISI) created by a channel with longer impulse response duration than that of the Cyclic Prefix (CP)as well as the Inter-Carrier Interference (ICI) resulting from high Doppler spreads is investigated. This is realized by simulation environment to utilize the advantages of modeling programs. In this simulation, Wavelet Transforms (WT) have been considered as alternative platforms for replacing Inverse Forrier Transform (IFFT) and FFT; all are programmed using MATLAB package. The simulation result shows that the ICI (ISI) power is significantly reduced. In this investigation,the effectof delay spread with 16-QAM and QPSK modulation schemes was studied. Results also show that our model, genetic based WP-OFDM, is superior as compared to WP-OFDM.